Groundwater contamination due to salt-panning activity and seawater intrusion at Tuticorin coastal zone, southern Tamil Nadu, India - Chelladurai, Singaraja; C, Chidambaram; P, Anandhan; K, Tariq Abdul Kareem (International Journal of Advanced Geosciences, 2014)
An attempt was made for the first time in the state of Tamil Nadu to assess the impact of saltpan and salt water intrusion effluent on available water sources existing in and around saltpans. A total of 48 water samples from different sampling sites were collected along coastal line and analyzed for physicochemical parameters such as Na+, Ca2+, Mg2+, K+, Cl-, SO2-4 and HCO-3 during Pre-monsoon. Results indicate both higher Cl- and SO2-4 concentration in water samples from salt pans than in water samples from other sources. In addition to ratio of Cl-/HCO-3 and Na+/Cl- were clearly indicated that relationships of salt pan contamination and seawater intrusion. It is also clearly evident that moles ratio of SO2-4/Cl- vs Cl- and ternary plot differentiated the salt pan and seawater contaminated in the study area. The result obtained conclusively suggests the detrimental impact of saline effluent on water quality in Tuticorin coastal area, rendering it unsuitable for the propagation of life and unfit for agricultural purpose. And this indicates a worse condition of salt pan vicinities, as the ground water is only source of drinking water in those places. Keywords: Saltpan; Seawater Intrusion; Physicochemical.